Ekspresi Keberagamaan Komunitas Terang Jakarta dalam Perspektif Popular Culture - Fadhila, Nurul; Hermansah, Tantan; Rizky, Kiky (INTERAKSI PERADABAN: Jurnal Komunikasi dan Penyiaran Islam, 2021)
The term "hijrah" is currently one of the models of religious expression that is trending in some urban youth. Hijrah is seen as a process of someone making a spiritual and religious leap. The "Terang Jakarta" (TJ) Community is one of the "hijrah" communities of the younger generation in Indonesia. TJ facilitates its community in a variety of Islamic study activities that are packaged in a structured, interesting, and up-to-date manner. So that in the TJ community, studying religion becomes fun or popular. This study wants to see how the religious expression of the TJ community is from the perspective of popular culture. The method used in this study is a qualitative method with an interpretive and naturalistic approach. The theory used is Emile Durkheim's religious expression and the theory of popular culture by Dominic Strineti. The results of this study indicate that the "hijrah" with all its supporting attributes which has been a trend is one of the religious expressions shown by the TJ community who adopted popular culture. The popular culture which is identical to something trendy, phenomenal, boisterous, hits, present, seems to lead to the expressions that exist in the management, members, and worshipers as well as various activities of the TJ community. Found many characteristics of popular culture adopted by this TJ community, so that the phenomenon of "hijrah" in this community can be said as part of popular culture.